Mitochondrial dysfunction in neurological disorders: Exploring mitochondrial transplantation - Pedro Norat (Nature Portfolio, 2020)
Abstract Mitochondria are fundamental for metabolic homeostasis in all multicellular eukaryotes. In the nervous system, mitochondria-generated adenosine triphosphate (ATP) is required to establish appropriate electrochemical gradients and reliable synaptic transmission. Notably, several mitochondrial defects have been identified in central nervous system disorders. Membrane leakage and electrolyte imbalances, pro-apoptotic pathway activation, and mitophagy are among the mechanisms implicated in the pathogenesis of neurodegenerative diseases, such as Alzheimer’s, Parkinson’s, and Huntington’s disease, as well as ischemic stroke. In this review, we summarize mitochondrial pathways that contribute to disease progression. Further, we discuss pathological states that damaged mitochondria impose on normal nervous system processes and explore new therapeutic approaches to mitochondrial diseases.